O humor na sitcom Seinfeld : a (re)construção de sentidos nas traduções das legendas para o português - Teixeira, Walkiria França Vieira e (2009)
This study investigate the translation of humorous situations in the subtitling of Seinfeld s episodes - a sitcom based in the American way of life and criticizing their middle-class morals, with characters involved into plots and their tries to solve the problems occurred in a non conventional way, breaking the societal rules and causing unusual results. We investigate the mechanisms used by the translator to transfer the humor to another reality and show the funny situations from the American cultural context to the Brazilian culture and if the funny situations are coherent in another cultural context. We start from the point that it occur losses of meaning in the (re)signification or (re)construction process of the humor signification in the episodes subtitling translation, when the subtitling are translated into Portuguese. We try to understand the role of the image in the arrangement of the humor showed in the episodes and if the scenario, the images represented associated to the subtitling became a supplementary element to the understanding of what is been shown to the TV watcher. We examine its adequacy to the translation, the adequacy of the humor and its intercultural and interlinguistic equivalences, the translation of humor and the subtitling. We based this work in the studies of humor made by Bergson (1978), Propp (1992) and Raskin (1985), the contributions made by Possenti (1998), Tagnin (2005a, 2005b), Chiaro (2006) and Travaglia (1989a, 1990) and the humor in the cultural contexts; in the translations studies made by Nida (1964), Catford (1980) and Bassnett (2003), and in the translation of humor made by Rosas (2002). We complete our study showing some aspects of subtitling translation to movies and TV and subtitling, made by Taflinger (1996), Grimm (1997), Araújo (2004), Toschi (1983), among others. We found out that the ambiguities, polissemic occurrences, word plays, irony, incongruities presented in the episodes are part of the problems found by the translator, and as consequences, the humorous scenes represented in the original episodes are not repeated into Portuguese with the same humoristic emphasis because these involve cultural and linguistic aspects. In this way we recognize that what seems funny in a cultural context of one country could not have the same connotation in another country due to linguistic and cultural questions.